The Importance of Wasathiyah Islam in Efforts to Maintain National Unity and Integrity - Khosiin, Khamam; Humaidi, M. Nurul (Journal of Social Science and Education Research, 2024)
Differences in ethnicity, culture, language, and religion are natural characteristics of any society. However, when these differences are not managed wisely, they can become sources of social friction. Disputes, conflicts, and even wars have often emerged from a failure to recognize and appreciate the richness that diversity brings. This lack of understanding stems from an inability to respect differences, leading to tension and division. One critical factor in preventing such conflicts is the cultivation of a proper understanding of religion, as religion significantly influences human behavior and decision-making in daily life. A correct religious understanding provides individuals with the moral compass needed to navigate complex social interactions, helping to foster mutual respect and tolerance. Therefore, it is essential that both religious understanding and practice be approached with moderation. This concept, often referred to as "wasathiyah" in Islam, emphasizes the importance of balance and avoiding extremism in any form. Wasathiyah encourages a middle path that embraces dialogue, tolerance, and cooperation between people of different backgrounds. By adopting a moderate stance in religious practice, individuals can contribute to a society that is more peaceful, tolerant, and harmonious. The benefits are far-reaching, as this approach promotes coexistence and reduces the likelihood of misunderstanding and conflict. Instead of viewing differences as threats, moderation allows people to see them as opportunities for growth and unity. Ultimately, a society built on the principles of moderation and mutual respect is one where diversity is celebrated, not feared.